Faktor-Faktor yang Mempengaruhi Stunting di Indonesia : Studi PRISMA (Preferred Reporting Items for Systematic Review & Meta Analysis). - Masdalena, Masdalena (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2024)
Stunting, a long-term nutritional problem that arises from insufficient food intake and is caused by vitamin deficiencies, has a broad and complex impact on children's health. Stunting can appear when the child is still in the womb and can occur until the child is two years old. This study explores the factors that influence stunting in Indonesia. Using the PRISMA (Preferred Reporting Items for Systematic Review & Meta-Analysis) method. Through a literature review from various sources such as Google Scholar and PubMed, this research aims to identify crucial factors related to stunting in toddlers by defining the keywords